2010
DOI: 10.1093/hmg/ddq397
|View full text |Cite
|
Sign up to set email alerts
|

The planar cell polarity gene Vangl2 is required for mammalian kidney-branching morphogenesis and glomerular maturation

Abstract: The planar cell polarity (PCP) pathway, incorporating non-canonical Wnt signalling, controls embryonic convergent (CE) extension, polarized cell division and ciliary orientation. It also limits diameters of differentiating renal tubules, with mutation of certain components of the pathway causing cystic kidneys. Mutations in mouse Vangl genes encoding core PCP proteins cause neural tube defects (NTDs) and Vangl2 mutations also impair branching of embryonic mouse lung airways. Embryonic metanephric kidneys also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
157
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(163 citation statements)
references
References 65 publications
4
157
1
1
Order By: Relevance
“…33,34 The PCP pathway also contributes to podocyte biology: Lp 2/2 mice display defects in glomerular morphology and maturation. 22,23 Glomerular defects observed in our new mouse with podocytespecific Vangl2 ablation are reminiscent to those seen in the Lp 2/2 mouse. From the published literature and our observations, we propose that podocytespecific deletion of Vangl2 may affect podocyte development through several mechanisms.…”
Section: Pcp Pathway and Glomerular Developmentsupporting
confidence: 54%
See 3 more Smart Citations
“…33,34 The PCP pathway also contributes to podocyte biology: Lp 2/2 mice display defects in glomerular morphology and maturation. 22,23 Glomerular defects observed in our new mouse with podocytespecific Vangl2 ablation are reminiscent to those seen in the Lp 2/2 mouse. From the published literature and our observations, we propose that podocytespecific deletion of Vangl2 may affect podocyte development through several mechanisms.…”
Section: Pcp Pathway and Glomerular Developmentsupporting
confidence: 54%
“…The knockdown of Vangl2 in cultured mouse podocytes affects filamentous F-actin arrangement and decreases the number of cell protrusions and cell motility 24 ; mild abnormalities in actin distribution in the Lp 2/2 glomerulus were also reported. 22 We, thus, propose that glomerular maturation defects seen in conditional Vangl2 and Lp embryos arise from suboptimal cytoskeletal arrangements within FPs. (2) We recently reported that loss of Vangl2 in cultured cells led to a decrease in nephrin internalization.…”
Section: Pcp Pathway and Glomerular Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from regulating the patterning of external epidermal structures such as wing hair cells in Drosophila and ciliary orientation, PCP controls embryonic convergent extension (CE), polarized cell division, cell direction and movement (Yates et al 2010a). dlg, scrib and lgl are essential for planar cell polarity (PCP), by establishing a cross-talk between apical-basal and planar cell polarity.…”
Section: Dlg Scrib and Lgl In Planar Cell Polaritymentioning
confidence: 99%